The lump of the medial canthus as diagnostic clue to cerebro-facial venous metameric syndrome: Report of a case - Mallio, Carlo Augusto (North Clin Istanb, 2020)
The Cerebro-Facial Venous Metameric Syndrome is characterized by ipsilateral venous/lymphatic anomalies involving simultaneously the brain and the face with a metameric distribution. This case report to describe a case of Cerebro-Facial Venous Metameric Syndrome presenting with a lump of the medial canthus. This was a case report a 24-year-old woman with a history of a mild headache, complained of a sporadic (at least once a month) serous leakage from the left eye and a small cutaneous protuberance in the left medial canthus, without focal neurological symptoms. The patient underwent brain Magnetic Resonance Imaging and findings were suggestive of a Cerebro-Facial Venous Metameric Syndrome 1-2. When multiple and ipsilateral vascular anomalies are observed, it should be considered the presence of Cerebro-Facial Metameric Syndrome, even without neurological symptoms and port-wine stains. Follow-up is mandatory, especially if there are cavernomas or facial arterio-venous malformations due to the risk of bleeding.